KEDUDUKAN MAHKAMAH KONSTITUSI SEBAGAI LEMBAGA NEGARA BERDASARKAN UNDANG-UNDANG DASAR 1945 - Johansyah, Johansyah (Solusi, 2019)
The Constitutional Court is the executive branch of the judiciary that is independent and separate from other branches of power, namely the government (executive) and legislative institutions. The Constitutional Court as a first and last level judiciary does not have an organizational structure as large as the Supreme Court which is the peak of a judicial system whose structure is vertically and horizontally covers five judicial environments, namely the general court environment, the state administrative court environment, the religious court environment, and military court environment. As an organ of judicial power that operates the judicial function, the Constitutional Court is independent, both structurally and functionally. The functions and authorities of the Constitutional Court based on Law No. 24 of 2003, namely the Constitutional Court has the authority to hear: Test the laws against the Republic of Indonesia 1945 Constitution; Decide on authority disputes between state institutions whose authority is granted by the Republic of Indonesia 1945 Constitution; Decide the dissolution of political parties; Decide disputes about election results; Give a verdict on the opinion of the House of Representatives that the President and / or Vice-President are suspected of violating the law in the form of treason, corruption, bribery, other serious crimes, or despicable acts, or no longer fulfill the conditions as President and or Vice President, as intended in the Republic of Indonesia 1945 Constitution.